Quality Evaluation of the Modified Diesel-Electric Train (KRDE) - Taufik Hidayat; Hilman Syaeful Alam (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2013)
Quality of the diesel-electric train (KRDE) modified from the electric train (A and B types) which were used in three operating regions in the Indonesian Railway Company has been evaluated by analyzing the cause of the KRDE damages in terms of some aspects including: design, components quality, maintenance (method, finance, human resources), environment and way of operation. Based on the evaluation, it was found that the modification of the both types of KRDE provided a very low reliability and availability due to design and technical problems, as well as unoptimal maintenance. In KRDE type A, damage occurs in the cabling system, compressor, radiator fan system, and the braking system. While in type B, damage occurs in the traction motors, static inverter, and radiator fan. It is predicted that their life span can not reach the design life of 25 years, and even they are expected to be grounded. Many improvement is required to lengten their service life including: repair, modification, human resource competence, facilities, spare parts, maintenance and management.